1997
DOI: 10.1175/1520-0485(1997)027<0999:sfiitn>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Sharp Frontal Interfaces in the Near-Surface Layer of the Ocean in the Western Equatorial Pacific Warm Pool

Abstract: During the TOGA COARE rich horizontal temperature and salinity variability of the near-surface layer of the ocean in the western Pacific warm pool was observed. High-resolution measurements were made by probes mounted on the bow of the vessel in an undisturbed region at ϳ1.7-m depth during four COARE cruises of the R/V Moana Wave. The authors observed several tens of cases of periodic sharp frontal interfaces of width 1-100 m and separation 0.2-60 km. The sharp frontal interfaces were often found in frontal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 33 publications
3
31
0
Order By: Relevance
“…As a near-surface low-density plume propagates into the stratified environment, internal waves can be excited in the thermocline. This can lead to a resonant interaction between the internal waves and the near-surface current, which results in a fragmentation of the buoyancy-driven current at the surface as observed in laboratory experiments (Simpson, 1987) and in the open ocean (Soloviev and Lukas, 1997). The fragmentation can become apparent as a banding pattern on the sea surface, as seen in the velocity field in our simulations (Fig.…”
Section: Near-surface Buoyancy-driven Currentssupporting
confidence: 61%
See 1 more Smart Citation
“…As a near-surface low-density plume propagates into the stratified environment, internal waves can be excited in the thermocline. This can lead to a resonant interaction between the internal waves and the near-surface current, which results in a fragmentation of the buoyancy-driven current at the surface as observed in laboratory experiments (Simpson, 1987) and in the open ocean (Soloviev and Lukas, 1997). The fragmentation can become apparent as a banding pattern on the sea surface, as seen in the velocity field in our simulations (Fig.…”
Section: Near-surface Buoyancy-driven Currentssupporting
confidence: 61%
“…This can lead to a fragmentation of the density current, as seen in laboratory experiments by Simpson (1987) and open-ocean observations by Soloviev and Lukas (1997). A buoyancy-driven current propagating into a two-layer stratified ambient environment in the coastal ocean may result in a resonant generation of an upstream undular bore (Grimshaw and Yi, 1991;Nash and Moum, 2005;White and Helfrich, 2012).…”
Section: Introductionmentioning
confidence: 95%
“…The asymmetry of freshwater plumes relative to the wind speed direction was observed in the western equatorial Pacific during TOGA-COARE (Soloviev and Lukas, 1997;Soloviev et al, 2002). Soloviev and Lukas (1997) suggested that this asymmetry can be explained by the mechanism of Stommel's (1993) Overturning Gate, schematically shown in Figure 7.…”
Section: Interaction Of Freshwater Plume With Wind Stressmentioning
confidence: 97%
“…The water flow in the leading edge of the gravity current and trailing fluid contains a complex pattern of three-dimensional motions (Özgökmen et al, 2004). Gravity currents may also interact with ambient stratification in a resonant way, leading to fragmentation of the near-surface lens, and with the surface wind stress, resulting in lens asymmetry in structure and mixing (Simpson, 1987;Soloviev and Lukas, 1997;Matt et al, 2014). The patterns in gravity currents are inherently three dimensional.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation